"I still have issues with pronunciation of words": A mixed methods investigation of the psychosocial and speech effects of Childhood Apraxia of Speech in adults. - Cassar, Courtney; McCabe, Patricia; Cumming, Steven (International Journal of Speech-Language Pathology, 2023)
Adolescents with Childhood Apraxia of Speech (CAS) are likely to have persistent speech errors compared to non-CAS peers (Lewis et al., 2018) and may have ongoing psychosocial issues (e.g. Carrigg, Parry, Baker, Shriberg, & Ballard, 2016). Beyond this, little is known about the long-term consequences of CAS in adulthood. This study explored whether adults who were reported to have had CAS as children have ongoing psychosocial or speech impacts. A cross-sectional descriptive design, with mixed-method analyses of demographic, psychosocial, and speech data was used. Data were collected via a four-part online survey. Part one consisted of questions about demographic information and participants' self-reported performance in speech, language and literacy. Parts two and three investigated the psychosocial impacts of CAS using the Brief Fear of Negative Evaluation Scale – Revised (BFNE- R) and The State-Trait Anxiety Inventory (STAI). Part four collected single word and connected speech data via an online audio recording, which was then transcribed following the Connected Speech Transcription Protocol (CoST-P). Analyses of speech characteristics reported in CAS was completed using Phon software. There were 17 participants in part one, 16 in parts two and three, and six in part four. Participants reported elevated levels of state (p = 0.01) and trait (p = 0.0001) anxiety compared to normative data. Ongoing segmental and suprasegmental speech errors were observed, with a significant difference between percent phonemes correct in single words versus connected speech (p = 0.03). Participants who provided a speech sample had difficulty with correct stress, use of juncture, and had increased intra- and inter-word segregation. Participants with better speech reported less anxiety. Psychosocial effects and speech characteristics associated with CAS in childhood appear to persist into adulthood. Confirmation of these results and research to determine treatment and psychosocial support needs past early childhood is warranted.